Respuesta :
x² - 6x + __ = 5 + __
to complete the square, you take your "middle" value, divide it by 2, then square it. in this case:
-6/2 = -3
(-3)² = 9
9 is the number you'd add to both sides to complete the square.
x² - 6x + 9 = 5 + 9
to complete the square, you take your "middle" value, divide it by 2, then square it. in this case:
-6/2 = -3
(-3)² = 9
9 is the number you'd add to both sides to complete the square.
x² - 6x + 9 = 5 + 9
The equation x^2 - 6x = 5 is a quadratic function, and we add 9 to both sides of the equation to complete the square
What is the completing the square?
The completing the square method of solving a quadratic function is a way of expressing the quadratic function as a perfect square
The equation is given as:
x^2 - 6x = 5
Take the coefficient of x
k = -6
Divide by 2
k/2 = -3
Square both sides
(k/2)^2 = 9
This means that we add 9 to both sides of the equation
Read more about completing the square at:
https://brainly.com/question/13981588